Urolithiasis pada Kucing Snow di K and P Clinic Surabaya - Ningsih, Awalul Fitria (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2023)
Urolithiasis is a disorder in the form of crystals or stones in the urinary tract such as the urinary bladder that occurs in both male and female animals. The condition of the formation of calculi due to supersaturation in urine consisting of one or several types of minerals. A case of urolithiasis in a Persian cat named Snow, female, 40 months old, 3.76 Kg, solid white hair color, came to the K and P Clinic and a physical examination was performed by palpation of the bladder which was filled with urine but not distended. Complete blood count (CBC) examination using blood samples showed leukocytosis, lymphocytosis, monocytosis, and thrombocytosis. The results of blood chemistry tests using blood serum samples showed hypoglycemic conditions and an increase in blood urea nitrogen (BUN) values. Calcium phosphate crystals are found on microscopic examination of the urine. Urinalysis test showed abnormal values ​​for ascorbic acid, microalbumin, protein, calcium, leukocytes, creatinine, blood, and protein to creatinine ratio. The formation of calculi looks like a hyperechoic mass and the presence of an acoustic shadow can be seen on ultrasonography (USG) examination of the urinary bladder. The handler given is cystotomy surgery. Keywords: Urolithiasis, calcium phosphate, ultrasound.